2022
DOI: 10.3390/molecules27020392
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Selenium on Bone Health: From Element to Therapeutics

Abstract: Osteoporosis, characterized by low bone mass and a disruption of bone microarchitecture, is traditionally treated using drugs or lifestyle modifications. Recently, several preclinical and clinical studies have investigated the effects of selenium on bone health, although the results are controversial. Selenium, an important trace element, is required for selenoprotein synthesis and acts crucially for proper growth and skeletal development. However, the intake of an optimum amount of selenium is critical, as bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 272 publications
1
28
0
1
Order By: Relevance
“…Na 2 SeO 4 and Na 2 SeO 3 were approved as feed additives in 1974, however, the situation was unsatisfactory so, just because Se-rich foods have been authorized by the Food and Drug Administration (FDA) does not always guarantee they are healthy options. When these permissions were granted, Se compounds such as SeMet were also missed (Yang et al, 2022[ 77 ]), and the only Se compounds available for animal feed at the stage of the regulatory action were the inorganic Se compounds. The first commercially accessible "high SeYeast" appeared in the mid-1970s.…”
Section: Selenium Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Na 2 SeO 4 and Na 2 SeO 3 were approved as feed additives in 1974, however, the situation was unsatisfactory so, just because Se-rich foods have been authorized by the Food and Drug Administration (FDA) does not always guarantee they are healthy options. When these permissions were granted, Se compounds such as SeMet were also missed (Yang et al, 2022[ 77 ]), and the only Se compounds available for animal feed at the stage of the regulatory action were the inorganic Se compounds. The first commercially accessible "high SeYeast" appeared in the mid-1970s.…”
Section: Selenium Supplementationmentioning
confidence: 99%
“…To the best of our knowledge, there have been at least ten studies that have looked at the relationship between nutritional or serum Se concentrations and BMD, osteoporosis, or osteoporotic fractures. A lack of Se is related to loss of bone mass in male rats and osteoarthropathy in Kashin Beck disease (KBD) (Yang et al, 2022[ 77 ]). This is because Se shortage interferes with the manufacture of many antioxidant SelPs, which compromises bone metabolism and causes osteoarthropathy.…”
Section: The Role Of Selenium In Different Diseasesmentioning
confidence: 99%
“…In recent years, research and developments on nanoparticles have been widely studied due to the investigation of their therapeutic properties and progressive application in modern medicine [ 1 , 2 , 3 , 4 ]. Nanoparticles have been incorporated on the surface of implants to improve the durability of implants by providing protective properties.…”
Section: Introductionmentioning
confidence: 99%
“…This takes place through various mechanisms. The main pathway regulating the balance between osteoblasts and osteoclasts is the RANK/RANKL/OPG system (receptor activator of nuclear factor κB/receptor activator of nuclear factor κB ligand/osteoprotegerin) [ 33 ]. Osteoprotegerin is a protein belonging to the family of tumour necrosis factor receptors (TNFR).…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis investigated whether there was a correlation linking bone condition with selenium concentration in the blood, selenium intake with meals, and the use of selenium supplements. The analysis included 21 studies: 10 cross-sectional studies; 6 case–control studies; 2 randomized, double-blind, placebo-controlled studies; 2 cohort studies; and 1 longitudinal study [ 33 ]. Most of the studies showed a positive link between selenium and bone health, BMD, and a reduced risk of osteoporotic fractures.…”
Section: Introductionmentioning
confidence: 99%